2017
DOI: 10.1007/s11764-017-0628-x
|View full text |Cite
|
Sign up to set email alerts
|

The pervasive nature of uncertainty—a qualitative study of patients with advanced cancer and their informal caregivers

Abstract: PurposeThe aim of this study was to explore the impact of extended cancer survival on broader aspects of life and wellbeing such as occupational, financial and family life for patients with advanced cancer and their nominated informal caregivers.MethodsIn-depth qualitative interviews were transcribed verbatim. A thematic framework was developed from an initial process of open coding and tested iteratively as new data were collected.ResultsTwenty-four patient-caregiver dyads with advanced ovarian (9), melanoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 59 publications
3
49
0
Order By: Relevance
“…Our finding regarding the overarching theme of 'uncertainties' is consistent with that of Shilling et al [33] with caregivers, i.e. uncertainties related to lack of control over the disease trajectory and to limitations in the ability to make plans for a future RTW were crucial obstacles for cancer survivors.…”
Section: Tensions From Uncertaintiessupporting
confidence: 88%
See 1 more Smart Citation
“…Our finding regarding the overarching theme of 'uncertainties' is consistent with that of Shilling et al [33] with caregivers, i.e. uncertainties related to lack of control over the disease trajectory and to limitations in the ability to make plans for a future RTW were crucial obstacles for cancer survivors.…”
Section: Tensions From Uncertaintiessupporting
confidence: 88%
“…Studies showed that financial worries and reduction in income are common among cancer survivors and can generate uncertainty about the future [33,46]. Owing to the relatively generous public welfare benefits in Norway, the participants in our study managed to maintain an adequate income during and after treatment.…”
Section: Macro-sociocultural Grrsmentioning
confidence: 99%
“…The influence on career aspiration and progression were not addressed at all; for example, the opportunity cost of a missed promotion at work [ 9 ]. Caregivers experience a sense that their own life is suspended, ‘on hold’ in some way; that the uncertainty around the length and quality of the patient's survival affects wide-ranging areas of life [ 10 13 ]. It is vital that this lack of control and altered sense of agency is better captured in caregiver outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…With maintenance therapy, patients may face a trade-off between the putative extension and quality of that survival [ 3 ]. Uncertainties about likely survival benefit can leave patients and their families unable, or unwilling to make plans for the future [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, QoS is not a static concept; it includes recognition that the relative importance of different dimensions will change across the disease trajectory. As such we designed the PROACT programme of work (Patient Reported Outcomes impact of Age and Carer role demands associated with Treatment) recognising that patients and their families are continually adjusting to a fluid situation whilst trying to maintain their ‘real world’ roles and responsibilities beyond cancer, such as caregiving responsibilities for a spouse or children/grandchildren, jobs and financial responsibilities [ 4 ].…”
Section: Introductionmentioning
confidence: 99%